IMPLEMENTATION OF SCOUTING ACTIVITIES THROUGH HANDICRAFT-BASED FIELD ENRICHMENT PROGRAMS AT PONDOK MODERN DARUSSALAM GONTOR - Muhammad Fathi Mubin; Reedho Muhammad Fathan; Muhammad Syakir Alfadhil; Moh Alwi Yusron; Syarifah Syarifah (STKIP Pesisir Selatan, 2026)
Objective: This study examines the implementation of scouting activities through handicraft-based Field Enrichment Practice (Praktik Pengayaan Lapangan/PPL) at Pondok Modern Darussalam Gontor and explores the supporting and inhibiting factors influencing its implementation. Methods: A qualitative case study was conducted using purposive sampling. Data were collected through observations, semi-structured interviews, and documentation involving PPL students, scout coaches, and supervisors. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while source and technique triangulation were employed to ensure data credibility. Results: The findings reveal that scouting activities were implemented systematically through planning, implementation, and evaluation stages. Handicraft-based activities promoted experiential learning by enhancing students' creativity, practical skills, teamwork, discipline, responsibility, leadership, and independence. Institutional support, structured mentoring, and active student participation facilitated successful implementation, whereas limited time, resource availability, and differences in students' abilities were identified as the primary challenges. Novelty: This study demonstrates that integrating handicraft-based scouting activities into the Field Enrichment Practice program provides an experiential learning model that simultaneously strengthens character education, practical competencies, creativity, and collaborative skills within the context of an Islamic boarding school.